Evaluation of a commercially available organic acid product on body weight loss, carcass yield, and meat quality during preslaughter feed withdrawal in broiler chickens: A poultry welfare and economic perspective - Menconi, A.; Kuttappan, V. A.; Hernandez-Velasco, X.; Urbano, T.; Matte, F.; Layton, S.; Kallapura, G.; Latorre, J.; Morales, B. E.; Prado, O.; Vicente, J. L.; Barton, J.; et al. (Oxford University Press, 2014)
The effect of a commercial organic acid (OA) product on BW loss (BWL) during feed withdrawal and transportation, carcass yield, and meat quality was evaluated in broiler chickens. Two experiments were conducted in Brazil. Commercial houses were paired as control groups receiving regular water and treated groups receiving OA in the water. Treated birds had a reduction in BWL of 37 g in experiment 1 and 32.2 g in experiment 2. In experiment 2, no differences were observed in carcass yield between groups. Estimation of the cost benefit suggested a 1: 16 ratio by using the OA. In experiment 3, conducted in Mexico, significant differences on water consumption, BWL, and meat quality characteristics were observed in chickens that were treated with the OA (P < 0.05). These data suggest this OA product may improve animal welfare and economic concerns in the poultry industry by reducing BWL and improving meat quality attributes.
Keywords: organic acid; chicken; welfare; transportation; meat quality